Clinical pharmacist-initiated assessment and amelioration of appropriate antibiotic use in surgical units at a South Indian tertiary care hospital - A handshake approach - Kuruvilla, Ann Vazhayil; Madhan, Ramesh; Chandagal Puttaswamy, Madhu (The Journal of Infection in Developing Countries, 2023)
Introduction: Studies on the appropriateness of antibiotic use among surgical patients are limited in developing countries, notably in India. Therefore, we aimed to evaluate the inappropriateness of antibiotic use, demonstrate the impact of clinical pharmacist interventions and determine the predictors of inappropriate use of antibiotics in the surgical units of a South Indian tertiary care hospital. Methods: This was a 1-year prospective interventional study on in-patients of the surgical wards to determine the appropriateness of the prescribed antibiotics by reviewing medical records using available antimicrobial susceptibility test reports and medical evidence. When inappropriateness in antibiotic prescriptions was identified, the clinical pharmacist discussed and conveyed apt suggestions to the Surgeon. Bivariate logistic regression analysis was applied to evaluate its predictors. Results: Among the 660 antibiotic prescriptions of 614 patients that were followed and reviewed, about 64% were inappropriate. Most inappropriate prescriptions were witnessed in the cases that involved the gastrointestinal system (28.03%). Among the inappropriate cases, 35.29% were attributed to an excessive regimen of antibiotic use which marked the highest. Based on the category of use, most of the antibiotics were used inappropriately as prophylaxis (76.7%) followed by empirical (71.31%). The increase in the percentage of the appropriate use of antibiotics resulting from pharmacist intervention was 95.06%. There was a significant link between inappropriate antibiotic use and the presence of two or three comorbid conditions, the use of two antibiotics, and length of hospital stay of 6-10 days and 16-20 days (p < 0.05). Conclusions: An antibiotic stewardship program in which the Clinical pharmacist is an integral part along with well-framed institutional antibiotic guidelines must be implemented to assure appropriate antibiotic use.